Envisioning an Ecojustice Adult Education - Audrey M. Dentith (Adult Education Research Conference, 2014)
This paper outlines an ecojustice adult education and distinguishes it from adult environmental education. The ecological crisis is described and a call is made for adult educators to take the initiative to teach and learn about the ecological crisis. Adult education is perfectly poised to confront these issues yet little effort has been made in the field. Adult educators might envision ecojustice education within a larger social justice effort.